Artificial Intelligence (AI) Integration Training in The Creation of Innovative Learning Media - Mas, Sitti Roskina; Haris, Ikhfan; Aini, Nurul; Hilumalo, Sukma Pratiwi; Djuma, Laila (CV. TOTUS TUUS, 2026)
The digital era demands teachers to innovate in creating learning media. In response to this challenge, the community service team organized training on integrating Artificial Intelligence (AI) in the creation of innovative learning media. This community service activity aims to: (1) introduce the concepts and potential of AI in education, (2) train practical skills in using AI tools to create learning media, and (3) increase teachers' motivation to innovate. The training was conducted at MIT Al Ishlah Gorontalo, involving 47 teachers as participants. The method used was participatory, through a combination of material presentations, tutorials, and self-practice facilitated by the team. Based on pre-test and post-test results, there was a 75% increase in participants' understanding. Additionally, the satisfaction questionnaire recorded that 98% of participants felt the material delivered was relevant to their needs and they successfully created AI-based learning media prototypes during the workshop session. This activity proves that teachers' capacity in educational technology can be significantly enhanced through structured and applicative training, opening opportunities for digital transformation in the MIT Al Ishlah Gorontalo environment.